Water Sustainability for China and Beyond - Liu, Jianguo; Yang, Wu (Science (American Association for the Advancement of Science), 2012)
Despite investments in water infrastructure, China must address complex human-nature interactions to ensure supply and quality. A water crisis has prompted the Chinese government to develop an ambitious water conservancy plan. However, the plan may not achieve water sustainability and may cause unintended environmental and socioeconomic consequences, unless it accounts for complex human-nature interactions ( 1 ). Water shortages, for example, force people to find alternatives, such as treatment facilities, whose land and energy requirements aggravate food and energy production, which need large amounts of water. Other nations face similar challenges and share real water from China along international rivers and/or virtual water through trade. Water problems are particularly challenging in China, which has the largest population, fastest-growing economy, rising water demand, relatively scarce water, dated infrastructure, and inadequate governance. We highlight China's water crisis and plan, and then offer recommendations.